Introduction to Symposium: childhood studies in the Anthropocene. Issue 3 (3rd May 2020) - Kraftl, Peter; Taylor, Affrica; Pacini-Ketchabaw, Veronica
ABSTRACT: Childhood studies scholars have increasingly sought to examine the complex entanglements of children's lives with nonhuman materials, animals, plants and earthly processes. Doing so has enabled new insights into children's relationships with global challenges such as climate change. Now, researchers from many disciplines are reflecting critically upon whether such challenges can be obviously ascribed to human activity, suggesting that we are entering a new (geological) epoch: the Anthropocene. The present collection of papers offers a range of empirically-informed, critical and theoretical analyses of the (possible) relationships between children and the Anthropocene. This paper frames the key debates covered in the symposium, introducing recent scholarship in childhood studies and opening out critical reflections on the term 'Anthropocene'. It also provides an introduction to the papers making up the symposium.